COMPARISON OF ANALYTICAL SENSITIVITY AND SPECIFICITY OF REVERSE TRANSCRIPTION LOOP-MEDIATED ISOTHERMAL AMPLIFICATION (RT-LAMP) AND REVERSE TRANSCRIPTION POLYMERASE CHAIN REACTION (RT-PCR) FOR DETECTION OF LOCAL PESTIVIRUS A - Hammad-ur-Rehman1; A. Ahmad1; M. Rabbani; M. Y. Tipu3 (Journal of Animal and Plant Sciences, 2020)
The main aim of this study was to compare reverse transcription loop-mediated isothermal amplification (RT-LAMP) and reverse transcription polymerase chain reaction (RT-PCR) in order to determine their analytical sensitivity and specificity using local characterized Pestivirus A. In order to compare the sensitivity of RT-LAMP and RT-PCR, serial 10 fold dilutions containing 9.91 x 1010 to 9.91 x 10-2 copies of cDNA of Pestivirus A, were prepared and tested. RT-LAMP proved more sensitive and was able to detect 9.91x100 copies of cDNA compared to RT-PCR (9.91x101). Both RT-LAMP and RT-PCR were found equally specific as no cross reaction with bovine herpes virus was observed.  Present study showed that RT-LAMP assay is highly sensitive, specific, rapid and can be used as an alternative to conventional RT-PCR, for the detection of Pestivirus A.
Keywords: Pestivirus A; Sensitivity; Specificity; RT-LAMP; RT-PCR